Implementasi Prinsip Kredibilitas Website dalam Optimasi Konten Digital untuk Sekolah - Kholik, Abdul; Rizki, Menati Fajar; Zalikha, Nasya Rizqy; Anadyar, Arbifadhil Fikri; Maulydia, Farah Widari; Syahdan, Mohammad Arsha (Penerbit Goodwood, 2025)
Purpose: This community service activity aims to implement website credibility principles in digital content optimization for SMK Pelita Alam (Pelita Alam Vocational High School). Methodology/approach: The method used was Community-Based Participatory Action Research (CBPAR) involving 11 participants consisting of the principal, teachers, administrative staff, and IT coordinator. Evaluation was conducted using a Website Credibility Checklist that includes 10 credibility aspects with 80 indicators. Results/findings: The evaluation results showed an overall credibility score of 52% (moderate category), with the security & privacy aspect achieving the highest score (88%) and the achievements & accomplishments aspect the lowest (25%). Three main improvement priorities identified were: human resource credibility (38%), achievements and accomplishments (25%), and current content & quality assurance (38%). Conclusions: This activity successfully increased the website management team's understanding of the importance of digital credibility and provided a systematic improvement roadmap to enhance the image and public trust toward the vocational education institution. Limitations: The evaluation was limited to internal stakeholder perspectives and did not include user feedback from external audiences such as students or parents. Contribution: This program contributes a replicable model for evaluating and improving digital credibility within educational institutions, combining participatory methods and measurable website indicators.